GPS Profiles Fimbulisen Ice Shelf 2009-2012 - Kohler, Jack; Melland, Gudmund; Dens, Ruben (Norwegian Polar Institute, 2016)
GPS profile collected along the route of the Fimbulisen ice shelf research project 2009-2012. ### Instruments - Trimble R7 dual-frequency GPS receiver - Trimble 5700 dual-frequency GPS receiver - Zephyr geodetic antennas